IMPROVING STUDENTS' ENGLISH SKILL THROUGH NUMBERED HEADS TECHNIQUE (A CLASSROOM ACTION RESEARCH AT THE SECOND YEAR STUDENTS OF SMP 8 MUHAMMADIYAH SURAKARTA IN 2009 / 2010 ACADEMIC YEAR) - MUTHIAH, KHOTIM (2010)
This research aims at describing the implementation of numbered Heads technique in teaching English, and describing the improvement of students' English skill through Numbered heads technique. The research paper is action research in which the data are in the form of field note, interview script, and students' worksheet. The research was done on March until June 2010 in SMP Muhammadiyah 8 Surakarta. The researcher took 31 students as the object. The researcher gets the data from events, informants and document. While the techniques of collecting data are observation, interview, and document. The result of the research shows that the implementation of Numbered Heads technique to teach English for the second year students of SMP Muhammadiyah 8 Surakarta is successful. It can be seen from every cycle where the students were always active in joining the teaching and learning process. By being given such questions and instructions related to the material, they could have good understanding about the material itself. By implementing Numbered Heads technique, the students' English skill is improved. It can be seen from the score of students in pre-test and post-test with passing grade 60. The pre-test, there are 7 students or 28% who pass the test. While in the post-test, there are 22 students or 88%. The number of the improvement is about 60%. The improvement of students English skill through Numbered Heads also can be seen from the result of calculating the mean of pre-test and post-test. It shows the improving pre test mean (53, 68) to the post test mean (74, 12). The number of improvement is about 20, 44 drawn from the subtraction of post-test with pre-test mean.